UPAYA PENINGKATAN PENGETAHUAN KADER TIM PENDAMPING KELUARGA (TPK) DALAM PERCEPATAN PENURUNAN STUNTING DI KECAMATAN PASAR KOTA JAMBI - Derniati, Neris; Fitriani, Fitriani; Siregar, Sri Astuti; Butar Butar, Marta; Gani, Abdul (Jurnal Salam Sehat Masyarakat (JSSM), 2024)
Stunting is the result of the interaction of various factors, namely insufficient food intake and increased nutritional needs. The purpose of this service activity is to improve the performance of the Family Assistance Team (TPK) cadres as the spearhead in efforts to accelerate stunting reduction in Telanaipura sub-district, Jambi City. This activity uses a qualitative approach related to optimizing the performance of the Family Assistance Team (TPK) cadres with counseling in an effort to accelerate stunting reduction. Overall, this intervention can accelerate the reduction of stunting in Pasar Sub-district, Jambi City. Improving the performance of the Family Support Team (TPK) administrators who foster families is expected to have a positive impact on efforts to reduce stunting in the Pasar District of Jambi City. This success can serve as an example for similar efforts in other areas experiencing stunting. The success of this activity shows the importance of careful planning, providing relevant and interactive materials, and effective follow-up. The experience of this activity will serve as a reference for future awareness activities, and is expected to make a major contribution to broader efforts to reduce stunting.